Soft Tissue Stability around Single Implants Inserted to Replace Maxillary Lateral Incisors: A 3D Evaluation. (19th May 2016) - Mangano, F. G.; Luongo, F.; Picciocchi, G.; Mortellaro, C.; Park, K. B.; Mangano, C.
Abstract : Purpose . To evaluate the soft tissue stability around single implants inserted to replace maxillary lateral incisors, using an innovative 3D method. Methods . We have used reverse-engineering software for the superimposition of 3D surface models of the dentogingival structures, obtained from intraoral scans of the same patients taken at the delivery of the final crown (S1) and 2 years later (S2). The assessment of soft tissues changes was performed via calculation of the Euclidean surface distances between the 3D models, after the superimposition of S2 on S1; colour maps were used for quantification of changes. Results . Twenty patients (8 males, 12 females) were selected, 10 with a failing/nonrestorable lateral incisor ( test group: immediate placement in postextraction socket) and 10 with a missing lateral incisor ( control group: conventional placement in healed ridge). Each patient received one immediately loaded implant (Anyridge®, Megagen, Gyeongbuk, South Korea). The superimposition of the 3D surface models taken at different times (S2 over S1) revealed a mean (±SD) reduction of 0.057 mm (±0.025) and 0.037 mm (±0.020) for test and control patients, respectively. This difference was not statistically significant ( p = 0.069). Conclusions . The superimposition of the 3D surface models revealed an excellent peri-implant soft tissue stability in both groups of patients, with minimal changes registered along time.